2010
DOI: 10.1021/ac902162e
|View full text |Cite
|
Sign up to set email alerts
|

Amperometric Immunosensor for Carcinoembryonic Antigen in Colon Cancer Samples Based on Monolayers of Dendritic Bipodal Scaffolds

Abstract: Detection of proteins that signal the presence or recurrence of cancer is a powerful therapeutic tool for effective early diagnosis and treatment. Carcinoembryonic antigen (CEA) has been extensively studied as a tumor marker in clinical diagnosis. We report on the development of an amperometric biosensor for the detection of CEA based on the immobilization of anti-CEA monoclonal antibody on a novel class of bipodal thiolated self-assembled monolayers containing reactive N-hydroxysuccinimide (NHS) ester end gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 36 publications
0
48
0
Order By: Relevance
“…With an extendedgate area of 62 μm × 126 μm and a transistor size of W/ L = 18 μm/1 μm, the coupling coefficient was 0.85 for the EGFET with passivation. Our pilot study indicated that the potential change induced by the RCA process might reach the order of 150 mV at the polygate of the EGFET [34]. Therefore, no amplification of the EGFET signal was required.…”
Section: The Egfet Sensors With Monolithically Integrated Circuitsmentioning
confidence: 94%
“…With an extendedgate area of 62 μm × 126 μm and a transistor size of W/ L = 18 μm/1 μm, the coupling coefficient was 0.85 for the EGFET with passivation. Our pilot study indicated that the potential change induced by the RCA process might reach the order of 150 mV at the polygate of the EGFET [34]. Therefore, no amplification of the EGFET signal was required.…”
Section: The Egfet Sensors With Monolithically Integrated Circuitsmentioning
confidence: 94%
“…Carcinoembryonic antigen (CEA) is known as a serum cancer biomarker associated with colon cancer, lung cancer, breast cancer, and other cancer in clinical tests [12,13]. Normal CEA Dept.…”
Section: Introductionmentioning
confidence: 99%
“…of Physics, Kyungpook National Unversity NS-1, 80 Daehakro, Bukgu, Daegu, 41566, Korea + level for healthy people lies between 3 ng/ml and 5 ng/ml, and the CEA level can increase up to 10 ng/ml due to other benign diseases. If the CEA level is over 20 ng/ml, then the cancer patients are considered to be in metastatic state [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical immunosensor is an alternative approach for CEA determination with the advantages of low detection limit, fast response, simple design and ease of miniaturization. [4][5][6][7] The development of a simple and effective strategy for immobilizing bioreagents on or into the electrode is a crucial step in the design and fabrication of electrochemical immunosensors. Recently, graphene and its derivatives have attracted wide attention in the applications of nanoelectronics, biomedicines and biosensors because of their remarkable conductivities, large surface areas and strong adsorption abilities.…”
Section: Introductionmentioning
confidence: 99%